2001
DOI: 10.1021/la001723z
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of CO and CO2 Adsorption on Tetragonal and Monoclinic Zirconia

Abstract: The adsorption of CO and CO2 on tetragonal and monoclinic ZrO2 was investigated using infrared spectroscopy and temperature-programmed desorption spectroscopy. For this study, samples were prepared of tetragonal ZrO2 (t-ZrO2) with surface areas of 20 and 187 m2/g and of monoclinic ZrO2 (m-ZrO2) with surface areas of 19 and 110 m2/g. The CO2 adsorption capacity of m-ZrO2 is more than an order of magnitude higher than that of t-ZrO2. The principal species observed on m-ZrO2 are HCO3 - and m- and b-CO3 2-, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
389
0
8

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 474 publications
(427 citation statements)
references
References 22 publications
30
389
0
8
Order By: Relevance
“…The first one should be the oxide phase, with basic properties, which attends to adsorb and activate CO2 molecules for running hydrogenation to methanol, through the formation of a formate as intermediate [46]. In more detail, the CO2 chemisorption can occur both via Zirconia Lewis basic sites [47,49,50], as well as by action of metal alkaline ZnO phase which enhances the affinity of Cu (+) -O to CO2 [18]. As proof, in our previous works we have attested a larger CO2 uptake, consequently to a greater concentration of basic sites [33,34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first one should be the oxide phase, with basic properties, which attends to adsorb and activate CO2 molecules for running hydrogenation to methanol, through the formation of a formate as intermediate [46]. In more detail, the CO2 chemisorption can occur both via Zirconia Lewis basic sites [47,49,50], as well as by action of metal alkaline ZnO phase which enhances the affinity of Cu (+) -O to CO2 [18]. As proof, in our previous works we have attested a larger CO2 uptake, consequently to a greater concentration of basic sites [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the catalyst performance depends on the right "deal" between the two catalytic functionalities [3,38,45,46,[49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies on the interaction with CO have been carried out using infrared spectroscopy 5,18,19,[22][23][24] . However, studies using other techniques, such as temperature-programmed methods 20,21,28,30 , calorimetry 27,31,32 , and gravimetry 33,34 , as well as theoretical studies 22,28 have been published.…”
Section: Introductionmentioning
confidence: 99%
“…This choice is made for simplicity and clarity, as monoclinic and tetragonal zirconias differ in, e.g., surface hydroxyl species 7,25 and acidity/basicity 7,24,30 , further demonstrated in their interactions with CO 7,25,30 and in their catalytic activity, e.g., in water-gas shift 11,12 . More information can also be found in the reviews by Dyrek et al 35 and Hadjiivanov 36 .Most of the pre-1993 works included in this paper were reviewed 20 years ago by Nawrocki et al 37 in the context of chromatography; this review is providing an update with work reported since 1993, from the perspective of catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this hypothesis, Pokrovski et al [60] found that, at the same temperature, much more CO or CO 2 per surface unit area can be chemisorbed on monoclinic than on tetragonal zirconia. More important for the discussion here, Li et al [54] detected a significantly higher uptake of SO 3 by monoclinic than by tetragonal zirconia at a temperature of 473 K. One may speculate that adsorbed SO 3 or sulfate will also reduce the difference in surface energies between the two phases and will, similar to water, diminish the particle size for the stability crossover.…”
Section: Effects Of Adsorbates On Oxide Surface Energy and Reactivitymentioning
confidence: 78%